Analisis Strategi Pemasaran Dalam Upaya Peningkatan Pendapatan di Era Setelah Pandemi pada Ahmad Dental Klinik - Zahra Dwi Anggraini; Nuryanto Nuryanto (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
This study aims to determine the right marketing strategy to increase revenue in the post-pandemic era and to determine the effectiveness of the marketing strategy implemented by Ahmad Dental Clinic in an effort to increase revenue in the post-pandemic era. This research method is qualitative with a SWOT analysis approach and data collection methods by observation, surveys, and interviews.The results showed that Ahmad Dental Clinic was in quadrant I with an SO value of 4.15. This condition supports Ahmad Dental Clinic in implementing digital marketing strategies and increasing service readiness as an internal strength to maximize existing external opportunities. This relates to the implementation of digital marketing strategies and the readiness of services provided in an effort to increase revenue in the post-pandemic era. Keywords: strategic management, marketing, effectiveness, revenue, pandemic